Optimization of bioaugmentation of the anaerobic digestion of Axonopus compressus cowgrass for the production of biomethane. (10th June 2020) - Lee, Jonathan T.E.; Wang, Qingkun; Lim, Ee Yang; Liu, Zhentian; He, Jianzhong; Tong, Yen Wah
Abstract: Lignocellulosic materials are the largest component of biomass in the world, and therefore suitable substrates for anaerobic digestion (AD). However, they are recalcitrant due to lignin-encrustation and the crystallinity of cellulose. Utilizing the wealth of knowledge in literature, this study compares different bioaugmentation strategies for the AD of Axonopus compressus, common name cowgrass, from single cultures to an engineered mix of three microbes with different functions. An optimization experiment is carried out on the biochemical methane potential with the best combination resulting in 20.7% more methane. The combination is then validated in a reactor operated semi-continuously, which increased production relative to the control after 18 days. The community dynamics of the bioaugmented reactor was tracked by Illumina MiSeq and compared against that of the control. The results prove that a properly engineered bioaugmentation is capable of increasing methane yield from a lignocellulosic substrate. Graphical abstract: Image 1 Highlights: Selection of bioaugmentation strategy – pure culture, double, or triple. Each microbe used is targeted at a stage in anaerobic digestion. Optimization of bioaugmentation using Taguchi's method revealed a combination that produced 20.7% more methane. Optimal combination was validated in semi-continuous setting.